2020
DOI: 10.1017/s0007123419000097
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis with Few Clusters: Improving Likelihood-Based Methods to Provide Unbiased Estimates and Accurate Inference

Abstract: Quantitative comparative social scientists have long worried about the performance of multilevel models when the number of upper-level units is small. Adding to these concerns, an influential Monte Carlo study by Stegmueller (2013) suggests that standard maximum-likelihood (ML) methods yield biased point estimates and severely anti-conservative inference with few upper-level units. In this article, the authors seek to rectify this negative assessment. First, they show that ML estimators of coefficients are unb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 34 publications
1
67
0
2
Order By: Relevance
“…work which argues that restricted maximum-likelihood estimation as well as significance thresholds based on Satterthwaite's Degrees of Freedom approximation result in valid estimates (Elff et al 2020).…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…work which argues that restricted maximum-likelihood estimation as well as significance thresholds based on Satterthwaite's Degrees of Freedom approximation result in valid estimates (Elff et al 2020).…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…Elff et al. (2021) showed in a simulation study that this method leads to unbiased estimates even with a few groups (and that estimates of group‐level variances were biased downward using standard maximum likelihood). We also compare the random intercept models with the fixed‐effects models in the “Sensitivity Analyses” section.…”
Section: Methodsmentioning
confidence: 99%
“…However, because the country-year sample is small with around 28-54 country-years, I selected the country-year controls carefully. A recent study has shown that multilevel models with a small number of upper level-units produce unbiased estimates and confidence intervals while using frequentist maximum likelihood estimators (Elff et al 2020). Nevertheless, the results should be interpreted with caution.…”
Section: Independent and Control Variablesmentioning
confidence: 97%